High palaeolatitude record of Late Maastrichtian – Early Danian climate change, Seymour Island, Antarctica - Frost, Peter Alan (University of Exeter, 2017)
The Latest Cretaceous period was characterised by global cooling, superimposed on this pattern of climate change were perturbations in global climate. In high palaeolatitude settings in the Southern Hemisphere short term glacial episodes may have occurred through the latest Cretaceous. The extensive sedimentary succession within the James Ross Basin, Antarctica, provided an opportunity to test the possibility of late Cretaceous glaciation in particular through the succession exposed on Seymour Island. A high resolution oxygen and carbon stable isotope record through the Late Maastrichtian – Early Danian was generated by analysing diagenetically unaltered aragonite nacre shell material from a molluscan fauna collected from the López de Bertodano Fm., part of the Marambio Group present on Seymour Island, Antarctica. The Marambio Group forms an extensive 1100 m thick Late Maastrichtian section that crops out over ~70 km2 of the southernmost part of the island. Coverage of stable isotope data for the measured stratigraphy was good with 213 screened analyses that included data from within 1 m of the K-Pg boundary located at 1029 m above datum, determined from the first occurrence of the dinoflagellate cyst Senegalinium obscurum. Stable isotope data (‰ VPDB) for primary aragonite from bivalves, cephalopods and gastropods exhibited screened stable isotope data ranges of -0.06 to +2.05‰ for δ18O and -7.54 to +3.7‰ for δ13C. Data showed that at individual stratigraphic levels the range in measured δ18O exhibited significant variability. Benthic specimens provided the majority of the stable isotope data, bivalves exhibited the widest range of δ18O and δ13C values. Data show that individual specimens from the same genus can exhibit significant variability for δ18O and δ13C and that analysis of single samples at discrete stratigraphic levels may provide an erroneous interpretation of climate change. Higher oxygen isotope values were seen mid-section and complement previous records of periods of cooler climate identified ...